"Throwaway" consumption in a consumerist society: Evidence from a developing country. Issue 1 (2nd July 2019) - Wijetunga, Dinuka
Abstract: Consumerism, closely linked with growth‐oriented development, has been identified as detrimental to environmental sustainability. Yet literature on throwaway consumption, a key form of unsustainable consumption, has rarely examined the influence of consumerist social values on individual behavior. This paper examines how the contemporary "liquid" consumerist social trends that elevate transience over durability manifest in individual throwaway consumption. Utilizing a sample of consumers from a developing country, Sri Lanka, the study explored the throwaway consumption of the mobile telephone. It identifies that consumers replace their phones with new ones at quick intervals because they consider novelty as a source of pleasure and technological change as progress, both of which can be considered as manifestations of "liquid" consumerism. Further, the market stimulates both ideas, providing greater impetus for throwaway consumption.